Fred and Wilma's Lucky Day - Marshall Anderson (Association of American Medical Colleges, 2008)
Abstract Introduction This resource is a biochemistry problem-based learning case suitable for either first- or second-year medical students. In this resource, two homeless people, Fred and Wilma, buy a Lotto ticket and win $100. To celebrate, they go drinking. Five days later, the money is gone and neither Fred nor Wilma has eaten anything during those five days. Medical students in a mobile clinic, who are performing a nutrition research project, examine them. Methods This is not a difficult case, but the students should be able to sink their teeth into it and go off in as many directions as they choose. For instance, they may concentrate on the metabolic pathways, metabolic acidosis, metabolic basis of the neurological disorders, or effects of vitamin deficiency on the various aspects of metabolism. Results This case has been used successfully in our problem based learning curriculum since 1990. Students have always rated the case high and have always commented that this was one case they will always remember. Discussion All the students will probably concentrate on the metabolism of ethanol and its effect on the body. Hopefully all groups will discover that there are actually two pathways for metabolizing ethanol and will find this unusual.